Anticancer Activity of Triazolo-Thiadiazole Derivatives and Inhibition of AKT1 and AKT2 Activation - Dimitrios T. Trafalis; Sofia Sagredou; Panayiotis Dalezis; Maria Voura; Stella Fountoulaki; Nikolaos Nikoleousakos; Konstantinos Almpanakis; Maria V. Deligiorgi; Vasiliki Sarli (MDPI AG, 2021)
The fusion of 1,2,4-triazole and 1,3,4-thiadiazole rings results in a class of heterocycles compounds with an extensive range of pharmacological properties. A series of 1,2,4-triazolo[3,4-b]-1,2,4-thiadiazoles was synthesized and tested for its enzyme inhibition potential and anticancer activity. The results show that 1,2,4-triazolo[3,4-b]-1,2,4-thiadiazoles display potent anticancer properties in vitro against a panel of cancer cells and in vivo efficacy in HT-29 human colon tumor xenograft in CB17 severe combined immunodeficient (SCID) mice. Preliminary mechanistic studies revealed that KA25 and KA39 exhibit time- and concentration-dependent inhibition of Akt Ser-473 phosphorylation. Molecular modeling experiments indicated that 1,2,4-triazolo[3,4-b]-1,2,4-thiadiazoles bind well to the ATP binding site in Akt1 and Akt2. The low acute toxicity combined with in vitro and in vivo anticancer activity render triazolo[3,4-b]thiadiazoles KA25, KA26, and KA39 promising cancer therapeutic agents.